Epigenetic deregulation of lamina-associated domains in Hutchinson-Gilford progeria syndrome - Köhler, Florian; Bormann, Felix; Raddatz, Günter; Gutekunst, Julian; Corless, Samuel; Musch, Tanja; Lonsdorf, Anke Susanne; Erhardt, Sylvia; Lyko, Frank; Rodríguez Paredes, Manuel (Genome medicine, 2020)
Hutchinson-Gilford progeria syndrome (HGPS) is a progeroid disease characterized by the early onset of age-related phenotypes including arthritis, loss of body fat and hair, and atherosclerosis. Cells from affected individuals express a mutant version of the nuclear envelope protein lamin A (termed progerin) and have previously been shown to exhibit prominent histone modification changes.
Gesehen am 23.03.2021